Association between rheumatoid arthritis and thyroid dysfunction: A meta-analysis and systematic review - Liu, Yi-jing; Miao, Hai-bing; Lin, Shu; Chen, Zhen (Frontiers in Endocrinology, 2022)
Objective: Rheumatoid arthritis (RA) is an autoimmune disorder. Multiple studies have investigated the risk of thyroid dysfunction in patients with RA but have reached conflicting conclusions. This systematic review aimed to determine whether patients with RA are at higher risk of thyroid dysfunction. Methods: We comprehensively reviewed online literature databases, including PubMed, Scopus, Embase, and the Cochrane Library, from their respective inception dates to March 25, 2022. Studies that provided data on at least one case of thyroid dysfunction in RA patients and their controls were included. Based on these data, we calculated pooled odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) for thyroid dysfunction in RA and non-RA patients. Results: Twenty-nine studies met the inclusion criteria, involving a total of 35,708 patients with RA. The meta-analysis showed that, compared with non-RA patients, RA patients had an increased risk of developing thyroid dysfunction, particularly hypothyroidism (OR 2.25, 95% CI 1.78–2.84). Subgroup analysis suggested that study type and sample source of control group were the source of heterogeneity. Conclusions: Patients with RA are at increased risk of developing thyroid dysfunction, especially hypothyroidism. Routine biochemical examination of thyroid function in RA patients should be strengthened. Larger prospective studies are needed to explore the causal relationship between RA and thyroid dysfunction, and to investigate the impact of thyroid dysfunction on RA disease activity, drug efficacy, and medication safety. Funding: The Science and Technology Bureau of Quanzhou [grant number 2020CT003, 2017Z009]; the Natural Science Foundation of Fujian Province [grant number 2020J01219].